Surgeon-Based 3D Printing for Microvascular Bone Flaps - Taylor, Erin M.; Iorio, Matthew L. (Journal of Reconstructive Microsurgery, 2017)
Background Three-dimensional (3D) printing has developed as a revolutionary technology with the capacity to design accurate physical models in preoperative planning. We present our experience in surgeon-based design of 3D models, using home 3D software and printing technology for use as an adjunct in vascularized bone transfer.Methods Home 3D printing techniques were used in the design and execution of vascularized bone flap transfers to the upper extremity. Open source imaging software was used to convert preoperative computed tomography scans and create 3D models. These were printed in the surgeon's office as 3D models for the planned reconstruction. Vascularized bone flaps were designed intraoperatively based on the 3D printed models.Results Three-dimensional models were created for intraoperative use in vascularized bone flaps, including (1) medial femoral trochlea (MFT) flap for scaphoid avascular necrosis and nonunion, (2) MFT flap for lunate avascular necrosis and nonunion, (3) medial femoral condyle (MFC) flap for wrist arthrodesis, and (4) free fibula osteocutaneous flap for distal radius septic nonunion. Templates based on the 3D models allowed for the precise and rapid contouring of well-vascularized bone flaps in situ, prior to ligating the donor pedicle.Conclusions Surgeon-based 3D printing is a feasible, innovative technology that allows for the precise and rapid contouring of models that can be created in various configurations for pre- and intraoperative planning. The technology is easy to use, convenient, and highly economical as compared with traditional send-out manufacturing. Surgeon-based 3D printing is a useful adjunct in vascularized bone transfer.Level of Evidence Level IV.
Keywords: 3D printing; medial femoral trochlea flap; medial femoral condyle flap; fibula flap